A Content Analysis of the English Reading Text's Appropriateness in the Pupil's Book of Action Pack Six in Jordan - Al-Zou'bi, Tahani; Smadi, Oqlah (Journal of Education and Practice, 2023)
Purpose: This study aimed at analyzing the reading texts of Action Pack Six in order to determine the extent that those reading texts are appropriate to the learners' level and environment. Methodology: A content analysis research tool was used to analyze all the reading texts in the textbook under study. Results: The content analysis showed that the reading texts in Action Pack Six are appropriate to the students' level and environment. Unique Contribution to Theory, Policy and Practice: It is recommended that more analysis should be conducted to other textbooks from the same series.